(untitled) (The Shivapuri Journal, 2026)
At the strategic level, a framework of counterinsurgency demands the synchronized application of instruments of national power—diplomatic, informational, military, and economic. The paper argues that since the threat group unleashing violence is targeting the state both militarily and politically, the strategy of counter must be designed to go beyond military measures and target the adversary comprehensively. This paper will use the framework to analyze Nepal’s internal conflict (1996-2006), as it makes an intriguing study for such use, albeit it is understood that any framework is only a guideline and requires continued modification.